A molecular clock regulates angiopoietin-like protein 2 expression. - Tsuyoshi Kadomatsu (PLoS ONE, 2013)
Various physiological and behavioral processes exhibit circadian rhythmicity. These rhythms are usually maintained by negative feedback loops of core clock genes, namely, CLOCK, BMAL, PER, and CRY. Recently, dysfunction in the circadian clock has been recognized as an important foundation for the pathophysiology of lifestyle-related diseases, such as obesity, cardiovascular disease, and some cancers. We have reported that angiopoietin-like protein 2 (ANGPTL2) contributes to the pathogenesis of these lifestyle-related diseases by inducing chronic inflammation. However, molecular mechanisms underlying regulation of ANGPTL2 expression are poorly understood. Here, we assess circadian rhythmicity of ANGPTL2 expression in various mouse tissues. We observed that ANGPTL2 rhythmicity was similar to that of the PER2 gene, which is regulated by the CLOCK/BMAL1 complex. Promoter activity of the human ANGPTL2 gene was significantly induced by CLOCK and BMAL1, an induction markedly attenuated by CRY co-expression. We also identified functional E-boxes in the ANGPTL2 promoter and observed occupancy of these sites by endogenous CLOCK in human osteosarcoma cells. Furthermore, Cry-deficient mice exhibited arrhythmic Angptl2 expression. Taken together, these data suggest that periodic expression of ANGPTL2 is regulated by a molecular clock.